2022
DOI: 10.3390/molecules27030758
|View full text |Cite
|
Sign up to set email alerts
|

Metal Complexes—A Promising Approach to Target Biofilm Associated Infections

Abstract: Microbial biofilms are represented by sessile microbial communities with modified gene expression and phenotype, adhered to a surface and embedded in a matrix of self-produced extracellular polymeric substances (EPS). Microbial biofilms can develop on both prosthetic devices and tissues, generating chronic and persistent infections that cannot be eradicated with classical organic-based antimicrobials, because of their increased tolerance to antimicrobials and the host immune system. Several complexes based mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 160 publications
(355 reference statements)
0
13
0
Order By: Relevance
“…Nowadays, bacterial infections and multi-drug resistance have become a matter of global concern, with many complexes being screened in order to overcome this issue [ 137 ]. Among the evaluated complexes, Zn(II) containing ones are taken into consideration due to the biocidal effect of this ion [ 138 ].…”
Section: Zinc(ii) Carboxylate Coordination Polymers Developed For Dif...mentioning
confidence: 99%
“…Nowadays, bacterial infections and multi-drug resistance have become a matter of global concern, with many complexes being screened in order to overcome this issue [ 137 ]. Among the evaluated complexes, Zn(II) containing ones are taken into consideration due to the biocidal effect of this ion [ 138 ].…”
Section: Zinc(ii) Carboxylate Coordination Polymers Developed For Dif...mentioning
confidence: 99%
“…Microbial biofilm development on tissues or medical devices represents an advantage in the case of bacterial pathogens, as they protect them from immune effector and antimicrobial substances and, simultaneously, are permanent reservoirs of infections, especially in the case of a medical device [11]. Therefore, biofilm inhibition is a major drug target for treating various bacterial and fungal infections.…”
Section: Resultsmentioning
confidence: 99%
“…We believe that unlike the CV tube adherence test, the CRA test is a much more subjective method. Among the most significant factors that influence the staphylococci ability to form biofilm are the type of surface and its characteristics, the site of development, microenvironmental conditions (humidity, temperature, ionic strength and pH), nutrient type and concentration, network design and composition, strain type and heterogeneity (Kramer et al, 2014;Olar et al 2022).This research has shown that the biofilm-forming ability was not connected with methicillin resistance in staphylococci and revealed a low percentage of staphylococcal strains (39.62% in CV tube adherence method and 44.12% in CRA method) that use both ways of protection against unfavorable external factors. These results are consistent with other studies that did not show association between antimicrobial resistance and the biofilm-forming capacity of staphylococci (Singhai et al, 2012, Cabrera-Contreras et al, 2013Chon et al, 2020;Tahaei et al, 2021).…”
Section: Discussionmentioning
confidence: 99%